The Association between Personal Characteristics and Educational Experiences with Academic Achievement among the Students Zanjan University of Medical Sciences - befrin MohammdZade; Leila Maghsodi; Mohamadmasoed Vakili; Tahereh Sadeghi; Fatemeh Zarei (Zanjan University of Medical Sciences and Health Services, 2017)
Background and Objective: Learning Strategies includes overt and covert behaviors, which are associated with success in learning. On the other hand, training students who are able to live in environments with diverse values, rapid technological changes, and developments in the socio-cultural complex is one of the unique challenges to a university administrator. Therefore, this study was performed to investigate the association of personal characteristics and educational experiences of the students of Zanjan University of Medical Sciences with their academic achievements. Materials and Methods: This descriptive correlational study was conducted on the students of Zanjan University of Medical Sciences during 2014-2015 academic year. Students were selected through random stratified sampling based on gender and discipline (N=352). The research tool was the college students' experiences questionnaire (CSEQ). Data was analyzed using descriptive statistics and multiple regression. Results: All three dimensions of college students' experiences, including perceptions of quality of environment, quality of effort, and social integration are significant anticipators of their academic achievements respectively and predict 0.415 of achievements variances. Conclusion: Taking into account the personal characteristics and educational experiences of college students for their academic achievements in medical universities is essential. In spite of the impact of academic environments ranging from individuals and facilities for college students, improving these factors contribute to better communication between students and faculty members and.